2018
DOI: 10.3842/sigma.2018.022
|View full text |Cite
|
Sign up to set email alerts
|

Poisson Algebras and 3D Superintegrable Hamiltonian Systems

Abstract: Abstract. Using a Poisson bracket representation, in 3D, of the Lie algebra sl(2), we first use highest weight representations to embed this into larger Lie algebras. These are then interpreted as symmetry and conformal symmetry algebras of the "kinetic energy", related to the quadratic Casimir function. We then consider the potentials which can be added, whilst remaining integrable, leading to families of separable systems, depending upon arbitrary functions of a single variable. Adding further integrals, in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…This paper has continued our work of [2,4,5] on building higher order integrals out of conformal symmetries, and, more generally, building Poisson algebras related to superintegrable systems. We emphasise that whilst all higher order integrals can be built out of Killing vectors in the constant curvature case, there was no such algebraic method available for more general spaces.…”
Section: Reduction To 2 Dimensional Systems: 4d Isometry Algebrasmentioning
confidence: 73%
See 2 more Smart Citations
“…This paper has continued our work of [2,4,5] on building higher order integrals out of conformal symmetries, and, more generally, building Poisson algebras related to superintegrable systems. We emphasise that whilst all higher order integrals can be built out of Killing vectors in the constant curvature case, there was no such algebraic method available for more general spaces.…”
Section: Reduction To 2 Dimensional Systems: 4d Isometry Algebrasmentioning
confidence: 73%
“…an example of the conformal algebra given in [4] (Table 3), corresponding to the case a 2 = a 3 = 2, a 4 = 0. The subalgebra g 1 , with basis (2a) is just a copy of sl (2).…”
Section: The 3d Euclidean Metric and Its Conformal Algebramentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining blocks are just the corresponding invariant subspaces. In [7] we showed that the 6-dimensional algebra g 1 + g 2 (which here we call g (0) ) has two quadratic Casimirs…”
Section: The 3d Euclidean Metric and Its Conformal Algebramentioning
confidence: 99%
“…In Section 2 we describe the structure of the 10-dimensional conformal algebra in this case, and show that it has a particular decomposition introduced in [7]. We show that this algebra has 4 involutive automorphisms, which play an important role in our calculations.…”
Section: Introductionmentioning
confidence: 99%